Effect of resveratrol and oxyresveratrol on deferoxamine-induced cancer stem cell marker expression in human head and neck squamous cell carcinoma - Artid Amorntaveechai; Thanaphum Osathanon; Prasit Pavasant; Sireerat Sooampon (Elsevier, 2022)
Objectives: Resveratrol and oxyresveratrol, a resveratrol derivative, possess various pharmacological activities, including anti-cancer activities. Because cancer stem cells play an important role in cancer recurrence, the aims of this study were to investigate whether resveratrol or oxyresveratrol can inhibit the expression of cancer stem cell markers under hypoxia. Materials and methods: Deferoxamine was used to mimic the hypoxic condition. The mRNA expression of cancer stem cell markers was analyzed by Real-time PCR. Flow cytometry was used to determine the number of CD-44+ and CD-105+ cells. Results: Deferoxamine dose-dependently induced the expression of cancer stem cell markers; Oct-4, Nanog, CD-44, CD-105, and CD-133. The induction of these cancer stem cells markers was inhibited when the cells were treated with either resveratrol or oxyresveratrol. Moreover, we found that resveratrol also reduced the number of CD-44+ and CD-105+ cells after deferoxamine treatment. Conclusions: Resveratrol and oxyresveratrol inhibit the expression of cancer stem cell markers and might target cancer stem cells in a hypoxia-associated tumor.